2014
DOI: 10.1051/0004-6361/201423992
|View full text |Cite
|
Sign up to set email alerts
|

A near-infrared spectroscopic survey of massive jets towards extended green objects

Abstract: Context. Protostellar jets and outflows are the main outcome of the star formation process, and their analysis can provide us with major clues about the ejection and accretion history of young stellar objects (YSOs). Aims. We aim at deriving the main physical properties of massive jets from near-infrared (NIR) observations, comparing them to those of a large sample of jets from low-mass YSOs, and relating them to the main features of their driving sources. Methods. We present a NIR imaging (H 2 and K s ) and l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
114
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(132 citation statements)
references
References 134 publications
(322 reference statements)
18
114
0
Order By: Relevance
“…Since outflow activity is expected to correlate with accretion activity (Caratti o Garatti et al 2015) the 10 4 year timescale of ejections could indicate alternating periods of accretion bursts and quiescence in AFGL 5142 MM1, consistent with timescales predicted for episodic accretion in low- (Stamatellos et al 2011) and high-mass stars (Meyer et al 2017). The short episodic ejection seen on a 10 year timescales (Section 3.4) would likely originate in the inner disk.…”
Section: Episodic Ejection In Afgl 5142supporting
confidence: 57%
See 1 more Smart Citation
“…Since outflow activity is expected to correlate with accretion activity (Caratti o Garatti et al 2015) the 10 4 year timescale of ejections could indicate alternating periods of accretion bursts and quiescence in AFGL 5142 MM1, consistent with timescales predicted for episodic accretion in low- (Stamatellos et al 2011) and high-mass stars (Meyer et al 2017). The short episodic ejection seen on a 10 year timescales (Section 3.4) would likely originate in the inner disk.…”
Section: Episodic Ejection In Afgl 5142supporting
confidence: 57%
“…In disk-jet systems, ejection rates correlate with accretion rates (Corcoran & Ray 1998;Caratti o Garatti et al 2015) -thus the ejection history of an MYSO allows inference of its accretion history -which is itself unobservable in a practical sense due to the timescales involved. Accretion history, based on ejection history, can therefore be used to compare low-and high-mass star formation.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows the continuum-subtracted Brγ-line photocentre displacements (with the errorbars in polar coordinates), which were derived from the astrometric solution in the different (radial) velocity channels (colour coded). Both the inner rim, defined by the study of the NIR continuum (see Kraus et al 2010), and the known jet axis (see Caratti o Garatti et al 2015a), are shown as a black solid ellipse and red solid line, respectively. The red dashed ellipses indicate the uncertainty on the size of the inner rim (1.97 ± 0.37 mas; Kraus et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Kraus et al 2010;Ilee et al 2013;Cesaroni et al 2014;Sanna et al 2015) with the parsec-scale jet and outflow emission being driven by the central accreting source (e.g. Sanna et al 2014;Caratti o Garatti et al 2015a). Moreover, compelling observational evidence for the accretion disc scenario has recently come from the detection of compact discs in Keplerian rotation (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation